Neutrophil "plucking" on megakaryocytes drives platelet production and boosts cardiovascular disease - Petzold, Tobias; Zhang, Zhe; Ballesteros, Iván; Saleh, Inas; Polzin, Amin; Thienel, Manuela; Liu, Lulu; Ul Ain, Qurrat; Ehreiser, Vincent; Weber, Christian; Kilani, Badr; Mertsch, Pontus; et al. (Immunity (Cambridge, Mass.), 2022)
Intravascular neutrophils and platelets collaborate in maintaining host integrity, but their interaction can also trigger thrombotic complications. We report here that cooperation between neutrophil and platelet lineages extends to the earliest stages of platelet formation by megakaryocytes in the bone marrow. Using intravital microscopy, we show that neutrophils "plucked" intravascular megakaryocyte extensions, termed proplatelets, to control platelet production. Following CXCR4-CXCL12-dependent migration towards perisinusoidal megakaryocytes, plucking neutrophils actively pulled on proplatelets and triggered myosin light chain and extracellular-signal-regulated kinase activation through reactive oxygen species. By these mechanisms, neutrophils accelerate proplatelet growth and facilitate continuous release of platelets in steady state. Following myocardial infarction, plucking neutrophils drove excessive release of young, reticulated platelets and boosted the risk of recurrent ischemia. Ablation of neutrophil plucking normalized thrombopoiesis and reduced recurrent thrombosis after myocardial infarction and thrombus burden in venous thrombosis. We establish neutrophil plucking as a target to reduce thromboischemic events.